A Dynamic Modeling Approach: Simplifying DFIG Theory, Simulation, and Analysis - Mehmet Dal; Ralph M. Kennel (Energies)
The operation and modelling of doubly fed induction generators (DFIGs) are quite different in grid-connected and stand-alone operated wind energy conversion systems (WECSs). Researchers usually simulate DFIGs in these operations using the pre-built models provided in commercial software, which are built using complex modeling techniques that most researchers in the field are unfamiliar with. In this paper, a simple and easy-to-use modeling approach based on the basic dynamic voltage equations of an induction machine (IM) is proposed to provide a more physical and practical understanding of the dynamic behavior of DFIGs, considering the difference between stand-alone and grid-connected operations. The basic theory and various dynamic models of DFIGs are reviewed and discussed to clarify the complexity of using alternative reference frame coordinates and various state variables in these models. A generic fifth-order DFIG model that is defined in an arbitrary general reference coordinate frame is considered. It is a flux-based model that allows for change in the parameters of the DFIG online and can be used only for grid-connected operations under control. In addition, this model is expanded to be used for stand-alone operation, but can also be used for grid-connected mode operation. The stand-alone model consists of a hybrid modeling approach and more closely resembles the real structure of a stand-alone DFIG system. The modeling technique used for the stand-alone DFIG provides a practical, non-mathematical way to solve the challenge of defining the dynamic equation of the stator voltage when different sizes and types of loads are connected to the stator. Many technical research problems and critical events that are challenging in DFIG-based WECSs can be studied using the proposed simulation models. As pioneering examples, several effective simulations are carried out, aiming to provide new researchers in this field with a more practical, in-depth, and intuitive understanding of the theory and operating principle of DFIGs in both stand-alone and grid-connected operations. The accuracy of the proposed stand-alone model is demonstrated by comparative simulation tests performed in parallel operation with two other pre-built models with the same conditions and power size. Furthermore, both proposed models are validated by simulating them for two different-sized DFIGs of 15 kW and 2 MW. In addition, a real experiment is conducted for the current controlled operation of a stand-alone DFIG using the introduced small-sized laboratory hardware setup. The results obtained through simulations and experiment are presented and discussed.